Flexible composite carbon fiber positive electrode carrier material for lithium-sulfur battery as well as preparation method and application of flexible composite carbon fiber positive electrode carrier material

By growing flexible composite carbon fiber cathode carrier material coated with ZIF-67 particles on the surface of cotton fibers and pyrolyzed at high temperature, the problems of poor conductivity of the positive electrodes of lithium sulfur batteries and the shuttle effect of lithium polysulfide are solved, high capacity and long cycle stability are achieved, and the preparation process is simplified.

CN119695167AActive Publication Date: 2025-03-25DALIAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510029868.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-03-25
Estimated Expiration
2045-01-08

AI Technical Summary

Technical Problem

The positive electrode active substance of lithium sulfur batteries has poor conductivity, and the shuttle effect of the reaction intermediate product lithium polysulfide leads to attenuation of battery capacity, and the traditional preparation method is complex and costly.

Method used

By growing coated cobalt-based metal organic frame (ZIF-67) particles on the surface of cotton fibers, cobalt elements are introduced to form a precursor of flexible composite carbon fiber material, and a lithium-sulfur battery flexible composite carbon fiber positive electrode carrier material is obtained through high temperature pyrolysis. This material passes through the physically confined domain of lithium polysulfide through the porous structure of cotton fibers, and promotes the conversion of lithium polysulfide through a cobalt carbon catalyst to weaken the shuttle effect.

Benefits of technology

The high initial specific capacity and long cycle stability of lithium-sulfur batteries are achieved, the preparation process is simplified, the material cost is reduced, and the battery is given flexibility.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695167A_ABST
    Figure CN119695167A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-sulfur battery flexible composite carbon fiber positive electrode carrier material and a preparation method and application thereof, and belongs to the technical field of new materials. In the preparation process of the material, cobalt-based metal organic framework (ZIF-67) particles are grown and coated on the surface of cotton fiber, so that a cobalt element is introduced, and a precursor of the flexible composite carbon fiber material is formed. And pyrolyzing to obtain the flexible composite carbon fiber positive electrode carrier material of the lithium-sulfur battery. The material can be used as a lithium-sulfur battery positive electrode after directly carrying sulfur, the synthesis process is simpler than that of the traditional lithium-sulfur battery positive electrode, the use of an organic solvent and a binder is avoided, and the effect of a flexible electrode is finally realized. Compared with a single carbon fiber flexible positive electrode, the ZIF-67 is carbonized to form cobalt-carbon catalyst particles to promote the conversion of lithium polysulfide, so that the shuttle effect of the lithium polysulfide is remarkably weakened, and good initial specific capacity and long cycle stability are shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a flexible composite carbon fiber positive electrode carrier material for a lithium-sulfur battery and a preparation method and application thereof, and belongs to the technical field of lithium-sulfur battery material preparation. Background Art

[0002] As a new type of efficient and environmentally friendly energy storage device, lithium-sulfur batteries are very important for improving energy utilization and realizing green and low-carbon concepts. This is mainly because compared with energy storage devices, lithium-sulfur batteries have a higher theoretical specific capacity (1675mAh·g -1 ), and it is low-cost, environmentally friendly, and has abundant sulfur reserves, which has broad application prospects in energy storage. As one of the main components of the battery, the flexible cathode carrier material can give the lithium-sulfur battery the property of bendability, thereby broadening the application scenarios of energy storage devices and being applied to the field of wearable devices.

[0003] However, lithium-sulfur batteries still have some shortcomings that hinder their further development. First, the conductivity of elemental sulfur and discharge products (Li2S and Li2S2) is low, which makes the electron transfer slow; secondly, the "shuttle effect" of the reaction intermediate product lithium polysulfide between the positive and negative electrodes causes the battery capacity to decay continuously; finally, the preparation method of the positive electrode of lithium-sulfur batteries not only requires the composite of carrier materials and elemental sulfur, but also requires the joint action of binders and solvents to form slurry and coat it on the current collector, just like traditional lithium-ion batteries. Therefore, there are problems such as complex preparation steps and high material costs.

[0004] In order to solve the problem of poor conductivity of the positive electrode active material of lithium-sulfur batteries and the shuttling of reaction intermediates, researchers usually use carbon materials as positive electrode sulfur-carrying materials to improve the conductivity of the positive electrode. Flexible carbon fiber, as a new type of positive electrode carrier material for lithium-sulfur batteries, can be directly compounded with sulfur and used as an electrode. Its preparation steps are simple, which reduces material costs and gives the battery the characteristics of a flexible electrode, which is very valuable for application. However, a single flexible carbon fiber only has a physical adsorption effect on lithium polysulfide, and it is difficult to effectively inhibit the shuttling of lithium polysulfide. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a lithium-sulfur battery flexible composite carbon fiber positive electrode carrier material and its preparation method and application, by growing and coating cobalt-based metal organic framework (ZIF-67) particles on the surface of cotton fibers, thereby introducing cobalt elements to form a precursor of a flexible composite carbon fiber material; and then pyrolyzing to obtain a lithium-sulfur battery flexible composite carbon fiber positive electrode carrier material. The inherent porous structure on the cotton fiber physically confines the shuttle of lithium polysulfide, and the growth and coating of cobalt-carbon catalyst particles catalyzes the conversion reaction of lithium polysulfide, greatly reducing the shuttle effect and improving the performance of lithium-sulfur batteries.

[0006] This material can be directly loaded with sulfur and used as the positive electrode of lithium-sulfur batteries. It is simpler than the traditional lithium-sulfur battery positive electrode synthesis process, avoids the use of organic solvents and binders, and finally achieves the effect of flexible electrodes. Compared with a single carbon fiber flexible positive electrode, ZIF-67 forms cobalt-carbon catalyst particles after carbonization, which promotes the conversion of lithium polysulfide, thereby significantly weakening the shuttle effect of lithium polysulfide, showing good initial specific capacity and long cycle stability.

[0007] In order to achieve the above-mentioned object, the present invention provides a lithium-sulfur battery flexible composite carbon fiber positive electrode carrier material and a preparation method and application thereof.

[0008] A flexible composite carbon fiber positive electrode carrier material for a lithium-sulfur battery, characterized in that:

[0009] (1) Cobalt element was introduced by growing and coating cobalt-based metal organic framework (ZIF-67) particles on the surface of cotton fibers to form a precursor of flexible composite carbon fiber materials.

[0010] (2) Through high-temperature pyrolysis, cotton fibers are transformed into a three-dimensional conductive network, the surface of which is evenly coated with cobalt carbon particles. The prepared material has good flexibility and can be directly loaded with sulfur and applied to the positive electrode of lithium-sulfur batteries without the addition of binders and conductive carbon black.

[0011] (3) The positive electrode material can effectively promote the conversion of lithium polysulfide and inhibit the shuttle effect during the charging and discharging process of lithium-sulfur batteries.

[0012] The above object of the present invention is achieved through the following technical solutions:

[0013] The first aspect of the present invention provides a lithium-sulfur battery flexible composite carbon fiber positive electrode carrier material and a preparation method thereof, comprising the following steps:

[0014] (1) Cobalt salt and 2-methylimidazole are added in a certain proportion to a certain amount of methanol solution to prepare a ZIF-67 precursor solution.

[0015] (2) Add the cleaned and dried cotton fiber cloth into the above precursor solution, soak it for a certain period of time, then take it out and dry it.

[0016] (3) The dried cotton fiber cloth is added into a mixed solution of methanol and ammonia water and allowed to stand for 24 hours to allow ZIF-67 to fully grow and coat the surface of the cotton fiber to obtain a composite cotton fiber material.

[0017] (4) The composite cotton fiber material is pyrolyzed at high temperature in a tubular furnace to obtain a flexible composite carbon fiber positive electrode carrier material for a lithium-sulfur battery.

[0018] In the flexible composite carbon fiber positive electrode carrier material for lithium-sulfur batteries and the preparation method thereof described in the present invention, the cobalt salt includes cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, cobalt chloride hexahydrate, etc. Preferably, it is cobalt nitrate hexahydrate.

[0019] In the flexible composite carbon fiber positive electrode carrier material for lithium-sulfur batteries and the preparation method thereof described in the present invention, the molar ratio of the cobalt salt to 2-methylimidazole is 1:3 to 8. Preferably, it is 1:3.

[0020] In the flexible composite carbon fiber positive electrode carrier material for lithium-sulfur batteries and the preparation method thereof described in the present invention, the amount of methanol required for the ZIF-67 precursor solution is directly related to the concentration of the cobalt salt, which is 0.6 to 2.8 mol / L. Preferably, it is 2.8 mol / L.

[0021] In the flexible composite carbon fiber positive electrode carrier material for lithium-sulfur batteries and the preparation method thereof described in the present invention, the volume ratio of ammonia water in the mixed solution of methanol and ammonia water is 33% to 75%, preferably 75%.

[0022] In the flexible composite carbon fiber positive electrode carrier material for a lithium-sulfur battery and the preparation method thereof described in the present invention, the cotton fiber cloth used in the step (2) has a size of 10 cm×10 cm.

[0023] Furthermore, the diameter of the cotton fiber is 10 to 30 μm.

[0024] Preferably, the diameter is 10 μm.

[0025] In the flexible composite carbon fiber positive electrode carrier material for lithium-sulfur batteries and the preparation method thereof described in the present invention, in the step (3), the particle size of ZIF-67 grown on the surface of cotton fibers ranges from 0 to 2 μm. Preferably, the particle size ranges from 500 to 1000 nm.

[0026] In the flexible composite carbon fiber positive electrode carrier material for lithium-sulfur batteries and the preparation method thereof described in the present invention, the high-temperature pyrolysis temperature in step (4) is 600-900°C, preferably 900°C.

[0027] Furthermore, the high temperature pyrolysis time is 1 to 3 hours.

[0028] Preferably, the high temperature pyrolysis time is 2 hours.

[0029] Another aspect of the present invention is to provide a lithium-sulfur battery, comprising the lithium-sulfur battery flexible composite carbon fiber positive electrode carrier material of the first aspect loaded with sulfur as a positive electrode material.

[0030] Furthermore, the positive electrode material is cut into circular electrode pieces with a diameter of 12 mm, and assembled with a separator, an electrolyte, a negative electrode piece, etc. into a lithium-sulfur battery.

[0031] Furthermore, 2 mg of elemental sulfur is uniformly loaded per square centimeter of the flexible composite carbon fiber positive electrode carrier material.

[0032] Furthermore, the electrolyte used was a mixed solution of DME:DOL (volume ratio of 1:1) in which 1M LiTFSI was dissolved and 1.0% LiNO3 was added, and the amount of electrolyte added to each battery was 30 μL.

[0033] The beneficial effects of the present invention are as follows: the present invention uses common cotton fiber cloth as a carbon source, introduces transition metal cobalt by growing and coating ZIF-67 on cotton fiber, and then pyrolyzes the flexible composite carbon fiber positive electrode carrier material at high temperature, and applies it to the positive electrode of lithium-sulfur battery. After carbonization, the cotton fiber cloth becomes a three-dimensional carbon fiber conductive network, which can enhance the electron transmission efficiency of the positive electrode. At the same time, the carbon fiber has a large number of pore structures, which can physically adsorb lithium polysulfide; and ZIF-67 becomes a cobalt-carbon catalyst after pyrolysis, which is coated on the surface of the carbon fiber. This unique structure can fully expose the cobalt active site, thereby participating in the catalytic conversion of lithium polysulfide, and because it is coated on the outside of the carbon fiber, it can also serve as a barrier to further block the diffusion of lithium polysulfide. Relying on the synergistic effect of the two, the lithium-sulfur battery has good charge and discharge performance. In addition, the flexible composite carbon fiber positive electrode material is different from the traditional positive electrode material, avoids the use of binders and organic solvents, and does not need to be attached to the current collector, thereby greatly simplifying the manufacturing process, reducing material costs, and having the characteristics of flexibility.

[0034] With the abundant hydroxyl active sites on the surface of cotton fibers, cobalt-based metal organic framework (ZIF-67) particles can grow and coat the surface of cotton fibers more evenly, thereby introducing cobalt elements before carbonization to form a precursor for flexible composite carbon fiber materials. Through a one-step high-temperature pyrolysis, cotton fibers become a three-dimensional conductive network with cobalt-carbon particles evenly coated on its surface. Compared with general cobalt oxide particles, ZIF-67-derived carbon materials have higher specific surface area and better conductivity, can provide abundant active sites, and accelerate electron transfer during the positive electrode reaction. The prepared material has good flexibility and can be directly applied to the positive electrode of lithium-sulfur batteries after sulfur loading, without the addition of binders and conductive carbon black. The positive electrode material can effectively promote the conversion of lithium polysulfide and inhibit the shuttle effect during the charge and discharge process of lithium-sulfur batteries.

[0035] Thanks to the introduction of cobalt-carbon catalyst particles, the lithium-sulfur battery using the flexible composite carbon fiber positive electrode material of the present invention has a higher specific capacity and cycle stability, showing an initial discharge specific capacity of 1352 mAh / g at a current of 0.2C. After 150 cycles, the remaining capacity is 876 mAh / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 These are digital photos of the materials in Example 1 and Comparative Example 1. Wherein, a is cotton, and b is ZIF-67@cotton.

[0037] Figure 2 This is a scanning electron microscope image of the cotton fiber cloth in Example 1.

[0038] Figure 3 The scanning electron microscope images of the materials in Example 1 and Comparative Example 1 are shown in FIG.

[0039] Figure 4 The scanning electron microscope images of ZIF-67@cotton prepared at different ratios of methanol to ammonia water in Examples 5-10.

[0040] Among them, a is the result of methanol:ammonia water = 5mL:15mL; b is the result of methanol:ammonia water = 10mL:10mL; c is the result of methanol:ammonia water = 20mL:10mL.

[0041] Figure 5 The characterization of the material CNTS obtained after carbonization in Comparative Example 1. Wherein, a is a digital photo of CNTS, and b is a scanning electron microscope image of CNTS.

[0042] Figure 6 The scanning electron microscope images of the materials involved in Example 1 and Comparative Example 1. Wherein, a is CNTS, and b is Co@CNTS.

[0043] Figure 7 This is the XRD pattern of the cotton fiber in Example 1.

[0044] Figure 8 This is the standard ZIF-67 XRD pattern.

[0045] Fig. 9 This is the XRD pattern of ZIF-67@cotton in Example 1.

[0046] Fig.10 This is the Co@CNTS diagram in Example 1.

[0047] Fig.11 This is a charge and discharge test diagram of CNTS as the positive electrode sulfur-carrying material of a lithium-sulfur battery in Comparative Example 1 at a current of 0.5C.

[0048] Fig.12 This is a charge and discharge test diagram of Co@CNTS as the positive electrode sulfur-carrying material of a lithium-sulfur battery at a current of 0.5C in Example 1.

[0049] Fig.13 This is a charge and discharge test diagram of Co@CNTS as the sulfur-carrying material for the positive electrode of a lithium-sulfur battery at a current of 0.2C in Example 1. DETAILED DESCRIPTION

[0050] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.

[0051] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.

[0052] Example 1

[0053] (1) Cut the cotton fiber cloth into a size of 10 cm × 10 cm, wash it with water and ethanol, and dry it for later use.

[0054] (2) 3.98 g of cobalt nitrate hexahydrate and 3.38 g of 2-methylimidazole were added to 5 ml of methanol to prepare a uniform solution.

[0055] (3) Immerse the cotton cloth in the above solution and evacuate the solution in a vacuum oven for 2 h. Then take out the cotton cloth and dry it in an oven at 60° C. for 4 h to obtain the cotton cloth loaded with MOF precursor.

[0056] (4) Add the cotton cloth loaded with MOF precursor into a mixed solution of 45 mL ammonia water and 15 mL methanol and let it stand for 24 h. After ZIF-67 particles fully grow on the cotton fiber surface, take it out and dry it to obtain ZIF-67@cotton.

[0057] (5) The cotton fiber with ZIF-67 was placed in a tube furnace, heated to 900°C at 5°C / min under an argon atmosphere, and kept at this temperature for 2 h. The flexible composite carbon fiber positive electrode carrier material was obtained, named Co@CNTS.

[0058] (6) The flexible composite carbon fiber positive electrode carrier material is cut and mixed with sulfur powder, placed in an oven, and the sulfur is melted at 155°C to obtain a flexible composite carbon fiber positive electrode sheet, which is then assembled into a lithium-sulfur battery.

[0059] Example 2

[0060] 3.98 g of cobalt nitrate hexahydrate and 3.38 g of 2-methylimidazole were added to 20 ml of methanol. Other conditions were the same as those in Example 1.

[0061] Embodiment 3-4

[0062] The cobalt nitrate hexahydrate in step (1) of Example 1 was replaced with cobalt acetate tetrahydrate and cobalt chloride hexahydrate. Other conditions were the same as those in Example 1.

[0063] Embodiment 5-10

[0064] The amounts of ammonia water and methanol in step (4) of Example 1 were adjusted to 15 mL ammonia water and 5 mL methanol; 30 mL ammonia water and 10 mL methanol; 10 mL ammonia water and 10 mL methanol; 20 mL ammonia water and 20 mL methanol; 10 mL ammonia water and 20 mL methanol; 15 mL ammonia water and 30 mL methanol. Other conditions were the same as those in Example 1.

[0065] Comparative Example 1

[0066] (1) Cut the cotton fiber cloth into a size of 10 cm × 10 cm, wash it with water and ethanol, dry it and set it aside, and name it cotton.

[0067] (2) The cotton fibers were placed in a tube furnace, heated to 900°C at 5°C / min under an argon atmosphere, and kept at this temperature for 2 h. A flexible carbon fiber positive electrode carrier material was obtained, named CNTS.

[0068] (3) Cut the flexible carbon fiber positive electrode carrier material and load sulfur to obtain a flexible carbon fiber positive electrode sheet, which is then assembled into a lithium-sulfur battery.

[0069] Figure 1 The digital photo comparison of cotton fiber cloth before and after ZIF-67 growth and coating in Example 1. After the cotton fiber cloth was grown and coated with ZIF-67, it showed obvious purple color and uniform coloring, which means that the prepared ZIF-67@cotton material has good uniformity and ZIF-67 is evenly attached to the cotton fiber cloth. Then the cotton fiber cloth was characterized by scanning electron microscopy ( Figure 2 ), it can be found that the cotton fiber cloth is a uniform three-dimensional network structure. Figure 3 As shown, the average diameter of a single fiber is 20 μm and the surface is smooth. When ZIF-67 grows on its surface, the surface of the cotton fiber is evenly covered with polyhedral particles of about 700 nm.

[0070] The effects of different ammonia concentrations on the growth of ZIF-67 on the cotton fiber surface are discussed in Examples 5-10. Figure 4 As shown, when the ammonia concentration is high (such as Figure 4 In a), a large number of ZIF-67 particles crystallize and grow outside the cotton fibers, and do not form a coating effect on the cotton fibers. This cannot provide a continuous conductive network as a positive electrode material for batteries after subsequent carbonization. Figure 4 In (c), only a small amount of ZIF-67 particles grow on the surface of cotton fibers, which is the main source of the positive electrode catalytic system of the battery. A small amount of ZIF-67 particles will weaken the catalytic effect. Therefore, the preferred ammonia:methanol ratio is 1:1, at which the coating effect of ZIF-67 on cotton fibers is the best (such as Figure 4 (b)

[0071] Figure 5The characterization of the material CNTS obtained after carbonization in Comparative Example 1. Among them, a is a digital photo of CNTS, and b is a scanning electron microscope image of CNTS; it can be seen from the figure that the CNTS obtained after carbonization exhibits a complete three-dimensional network structure, and the carbon fibers have a regular shape. Figure 6 The scanning electron microscope images of the materials involved in Example 1 and Comparative Example 1. Among them, a is CNTS and b is Co@CNTS; the figure shows that Co@CNTS still maintains a complete coating structure. XRD test shows obvious signal peaks of cobalt metal and its oxide peaks. At the same time, the carbon fiber is obviously graphitized, with a sharp peak at 26°. According to the XRD diagram, ( Figure 7 , 8 , 9), ZIF-67@cotton superimposed the signal peak of ZIF-67 on the XRD peak of cotton, which also proved the successful preparation of ZIF-67@cotton. After carbonization, Co@CNTS was obtained (its XRD is shown in Fig.10 shown).

[0072] The three-dimensional carbon fiber substrate after carbonization in Comparative Example 1 still has good flexibility. It is used as a sulfur-carrying material for the positive electrode of a lithium-sulfur battery and a cyclic charge and discharge test is performed at 0.5C. Fig.11 As shown, the initial discharge specific capacity at 0.5C is only 512 mAh / g, and the remaining capacity after 200 cycles is 375 mAh / g.

[0073] Similarly, the material in Example 1 was subjected to a cyclic charge and discharge test at 0.5C. The results are as follows: Fig.12 As shown in Figure 1, the material exhibits an initial discharge capacity of 868 mAh / g. After 200 cycles, the remaining capacity is 547 mAh / g, which is significantly better than the CNTS in the comparative example. Cyclic charge and discharge tests were also carried out at 0.2C; the results are shown in Figure 1. Fig.13 As shown in the figure, the material exhibits an initial discharge capacity of 1352 mAh / g, reaching the theoretical capacity of lithium-sulfur batteries (1675 mAh g -1 ) of 80.7%. After 150 cycles, the remaining capacity is 876 mAh / g, which is significantly better than CNTS in the comparative example. This shows that the flexible composite carbon fiber positive electrode carrier material in the presence of cobalt and its metal oxides has a significant promoting effect on the conversion of lithium polysulfide, thus showing excellent electrochemical performance compared with CNTS.

[0074] Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a flexible composite carbon fiber positive electrode carrier material for a lithium-sulfur battery, characterized in that: The following steps are involved: (1) adding cobalt salt and 2-methylimidazole into a methanol solution to prepare a ZIF-67 precursor solution; the molar ratio of the cobalt salt to the 2-methylimidazole is 1:3 to 8; (2) adding the cleaned and dried cotton fiber cloth to the ZIF-67 precursor solution, soaking it, taking it out and drying it; the concentration of cobalt salt in the ZIF-67 precursor solution is 0.6 ~ 2.8 mol / L; (3) adding the dried cotton fiber cloth into a mixed solution of methanol and ammonia water and allowing the mixture to stand, so that the ZIF-67 particles can fully grow and coat the surface of the cotton fiber to obtain a composite cotton fiber material; (4) The composite cotton fiber material is pyrolyzed at high temperature in a tubular furnace to obtain a flexible composite carbon fiber positive electrode carrier material for a lithium-sulfur battery.

2. The method for preparing a flexible composite carbon fiber positive electrode carrier material for a lithium-sulfur battery according to claim 1, characterized in that: The cobalt salt is one or more of cobalt nitrate hexahydrate, cobalt acetate tetrahydrate, and cobalt chloride hexahydrate.

3. The method for preparing a flexible composite carbon fiber positive electrode carrier material for a lithium-sulfur battery according to claim 1, characterized in that: In the step (2), the diameter of the surface fibers of the cotton fiber cloth is 10-30 μm.

4. The method for preparing a flexible composite carbon fiber positive electrode carrier material for a lithium-sulfur battery according to claim 1, characterized in that: In the mixed solution of methanol and ammonia water in step (3), the volume ratio of ammonia water to methanol is 3:1-1:

2.

5. The method for preparing a flexible composite carbon fiber positive electrode carrier material for a lithium-sulfur battery according to claim 1, characterized in that: The particle size of the ZIF-67 particles in step (3) is less than 2 μm.

6. The method for preparing a flexible composite carbon fiber positive electrode carrier material for a lithium-sulfur battery according to claim 1, characterized in that: In the step (4), the high temperature pyrolysis temperature is 600-900°C and the pyrolysis time is 1-3 h.

7. A flexible composite carbon fiber positive electrode carrier material for a lithium-sulfur battery, characterized in that: The method is prepared by any one of claims 1 to 6.

8. A positive electrode sheet for a lithium-sulfur battery, characterized in that: The positive electrode sheet is made of the composite carbon fiber positive electrode carrier material according to claim 7.

9. The positive electrode sheet of a lithium-sulfur battery according to claim 8, characterized in that: The positive electrode sheet is prepared after sulfur is loaded on a composite carbon fiber positive electrode carrier material, and each square centimeter of the flexible composite carbon fiber positive electrode carrier material is uniformly loaded with 2 mg of sulfur.

10. A lithium-sulfur battery, characterized in that: The battery comprises a positive electrode sheet, a separator, an electrolyte and a negative electrode sheet, wherein the positive electrode is the positive electrode according to claim 8 or 9; The electrolyte is a mixed solution of ethylene glycol dimethyl ether: 1,3-dioxolane in which lithium bis(trifluoromethanesulfonyl)imide and LiNO3 are dissolved, and the volume ratio of ethylene glycol dimethyl ether: 1,3-dioxolane in the mixed solution is 1:1.

Citation Information

Patent Citations

  • Double-carbon cloth flexible lithium-sulfur battery and preparation method thereof

    CN107994251A

  • Preparation method of positive material for cobalt nitride / porous carbon plate / carbon cloth self-supported lithium-sulfur battery

    CN108923030A

  • Co / carbon cloth-based lithium-sulfur battery positive electrode material and preparation method thereof

    CN113130883A

  • NiCoSe / carbon cloth / S composite lithium-sulfur battery positive electrode material and preparation method thereof

    CN114824275A